UJI EFEKTIVITAS KOMBINASI SARI BUAH MERAH (Pandanus conoideus Lam.) DAN PERASAN DAUN KUMIS KUCING (Orthosiphon aristatus Mig.) SEBAGAI ANTIINFLAMASI PADA MENCIT (Mus musculus) SECARA TOPIKAL - Sukriani Kursia; Besse Hardianti; Jeane Mega Tanna (Fakultas Farmasi UMI, 2015)
Inflammation is a protective response on the body from injury of cell. Edema is one of inflammation sign. It was reported that Pandanus conoideus Lam. and Orthosiphon aristatus Mig. empirically used as an antiinflammation. The aim of this research was determining the combination effect of Pandanus conoideus Lam. and Orthosiphon aristatus Mig. based on formation edema volume on sole of foot male mice againts carrageenan, inflammation that occurs is measured using the pletysmometer. In the research, we used sodium CMC as a negative control and sodium diclofenac as a positive control administered topically. While combination of Pandanus conoideus Lam. and Orthosiphon aristatus Mig. with a ratio of 2:1. The result showed decrease edema with percent of inhibition 76,92% Respectively, as a conclussion the result indicate Natrium diklofenak didn't showed significant effect compare with the testing data.